Health-Related Quality of Life: Longitudinal Analysis From the Time of Breast Biopsy Into the Post-treatment Period - Boivin, Michael J.; Sikorskii, Alla; Haan, Pamela; Smith, Stephanie S.; Symonds, Laura L.; Khattree, Ravindra; Giordani, Bruno; Blow, Adrian J.; Osuch, Janet R. (Frontiers in Global Women's Health, 2021)
ABSTRACT Background. Physical, psychological, social, and spiritual quality of life (QOL) may be affected by breast cancer diagnosis and treatment, with mixed findings for psychological quality of life and cognitive ability performance. The aim of the present study was to evaluate QOL in women over a period of one year from biopsy for a breast abnormality. Methods. Self-reported measures of physical, psychological, social, and spiritual QoL were obtained after biopsy results but prior to treatment initiation (baseline), four and 12 months later. CogState computerized neuropsychological screening battery also provided an evaluation of psychological QOL. Three groups of women: those with benign biopsy results, those with malignancy treated with chemotherapy, and those with malignancy not treated with chemotherapy were compared at four and 12 months after adjusting for baseline to isolate the effects of treatment. Additional covariates included age, level of education, and income. Results. Benign biopsy results group included 72 women, whereas malignancy was found for 87 women of whom 33 were treated with chemotherapy and 54 without chemotherapy. At the time of diagnosis, women with cancer had worse psychological and social, but better spiritual QOL than those with benign biopsy results. Only CogState monitoring accuracy was worse for women with cancer compared to controls at the time of biopsy results. After adjusting for QOL at baseline, women treated for cancer had worse physical and social QOL four and 12 months later. Psychological well-being was worse for women with cancer at month four but improved at one year. No differences in cognition were found at four and twelve months when adjusted for baseline cognition and covariates. Discussion. Breast cancer is a traumatic life event for women, negatively affecting psychological and social QOL domains, yet increasing spiritual QOL. Later, cancer treatment worsens physical, psychological, and social QOL compared to those without cancer. Conclusions. Our findings suggest that interventions to improve psychological QOL may be especially important at the time of cancer diagnosis, while interventions to improve physical well-being are most needed during and following cancer treatment. Support to improve social QOL is needed from the time of diagnosis into post-treatment survivorship.